Reconstructing the Meaning of Ni‘mah in Al-Hikam: Ibn ‘Ata’illah’s Perspective on Tazkiyat Al-Nafs - Muhammad Nailul Ma’arif; Nur Alif Arrokhim; Moh. Alfarizi Putra (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2026)
This study examines the concept of ni‘mah (divine blessing) in al-?ikam by Ibn ‘A??’illah al-Sakandar?, with a particular focus on its function as an instrument of tazkiyat al-nafs (purification of the soul). In many Islamic studies, ni‘mah has generally been understood within theological and moral frameworks as a divine gift that requires gratitude. Such perspectives tend to emphasize the outward and material dimensions of blessings while paying limited attention to their spiritual significance. Against this backdrop, this research aims to analyze Ibn ‘A??’illah’s reconstruction of the meaning of ni‘mah and its relevance to the spiritual crisis of modern society. This research employs a qualitative library-based method using a thematic-descriptive approach. The primary source of this study is al-?ikam, while secondary sources include books, journal articles, and previous studies related to Sufism and the concept of ni‘mah in Islam. The findings reveal that Ibn ‘A??’illah does not merely view ni‘mah as worldly pleasure or material prosperity, but rather as a spiritual medium that shapes inner consciousness, purifies human attachment to worldly matters, and directs the heart toward God. From this perspective, both ease and hardship can equally function as ni‘mah, depending on their impact on one’s spiritual condition. Furthermore, this study demonstrates that the concept of ni‘mah in al-?ikam remains highly relevant to modern challenges, particularly materialism, consumerism, and the growing crisis of spiritual meaning in contemporary life.